The Influence of Zone and Size of Sea Sand Aggregate on the Production of Self Compacting Concrete Technology - Adnan Adnan; Jasman Jasman; Salasiah Salasiah (Journal of Moeslim Research Technik, 2024)
The strength and durability that can be achieved by concrete depends on factors such as the quality of the aggregates. This study presents the effect of zone gradation and size of fine aggregates of sea sand as a mixing material for concrete production by the method of aggregate incorporation that will produce maximum compressive strength of concrete. The most important thing in the use of beach sand is the compressive strength of the concrete. If the compressive strength of the test is high, the other properties will be good. The factors that affect the compressive strength of concrete consist of the quality of materials, cement water, aggregates, working methods such as mixing, compaction and curing and the age of testing based on (SNI 03-6468-2000). The application of marine sand as a concrete mix will have a positive impact on coastal and island communities, which have difficulty obtaining sand from rivers.